2005
DOI: 10.1103/physrevlett.94.066103
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Multilevel Order in Supramolecular Assemblies

Abstract: The process of self-assembly at multiple length scales of bis-urea substituted toluene on a Au(111) surface was studied by low temperature scanning tunneling microscopy. Pattern formation is controlled by specific hydrogen bonds between these molecules but also by significantly weaker lateral coupling between the resulting supramolecular polymers and a quasiepitaxial interlocking with the substrate. The ordered assemblies exhibit a tunnel transparency. Our experiments indicate the necessity of multiple interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 24 publications
1
45
0
Order By: Relevance
“…Among a great variety of compounds which are able to form supramolecular polymers in solutions, N, N -dialkylureas (R-NH.CO.NH-R) take a special place [5][6][7][8][9][10][11][12]. Three active centers of the ureide group, -NH.CO.NH-, capable of forming the hydrogen bonds C=O.…”
Section: Introductionmentioning
confidence: 99%
“…Among a great variety of compounds which are able to form supramolecular polymers in solutions, N, N -dialkylureas (R-NH.CO.NH-R) take a special place [5][6][7][8][9][10][11][12]. Three active centers of the ureide group, -NH.CO.NH-, capable of forming the hydrogen bonds C=O.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the electrical, morphology, and spectral measurements, it can be deduced that some chemical or physical changes, such as disordering, and/or morphology modification, may occur pronouncedly at the Au/semiconductor interface and in its vicinity during the device operation and/or storage,31–38 which causes or accelerates the device degradation. It has been demonstrated that: i) Au can induce the modification of the molecular orbitals of pentacene, which may further lead to the breakdown of the delocalized molecular orbitals and ordered structure of the pentacene crystal film;31 ii) in actual metal/organic‐semiconductor contact systems, a substantial dipole layer may form at the interface, which will lead to a shift of the molecular energy levels and a change in the energy difference between the metal Fermi level and highest occupied molecular orbital (HOMO)/lowest unoccupied molecular orbital (LUMO) of the semiconductor;32, 33 (iii) dewetting and molecular reorganization may occur in organic thin films on the Au surface;34–36 and iv) Au atoms can react with p‐type (pentacene) and n‐type (PTDCA) semiconductors to form covalent metal‐organic complexes 37, 38. These phenomena may provide some clues (but maybe not the real reasons yet) to understanding the influence of Au electrodes on the device stability.…”
mentioning
confidence: 99%
“…Recently, polymer coatings with thicknesses in the nanometer scales have proliferated into many segments of modern technology including sensors, lithography, optoelectronics, and biological systems. However, the thin polymer films usually rupture by undergoing dewetting on an antagonistic surface upon annealing [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. This instability has been attributed almost exclusively to the dispersive force stemming from long-range van der Waals forces operative between the surfaces of the thin film, in a close analogy to the dewetting of low molecular weight liquid films [17][18][19].…”
mentioning
confidence: 99%